Człowiek i mistyka w ujęciu Evelyn Underhill - Mirosław Kiwka (Wrocławski Przegląd Teologiczny, 2020)
In the English-speaking world of the first half of the twentieth century Evelyn Underhill (1875-1941) was one of the most widely read writers on religion and spiritual practice, in particular on Christian mysticism. No other book of its type met with success to match that of her best-known work, Mysticism, published in 1911. She was conferred with an honorary Doctorate of Divinity from Aberdeen University and made a fellow of King’s College. She was the first woman to lecture to the clergy in the Church of England as well as the first woman to officially conduct spiritual retreats for the Church. She was also the first woman to establish ecumenical links between churches and one of the first woman theologians to lecture in English colleges and universities, as she did frequently. The paper aims at E. Underhill’s understanding of mysticism. Beginning with the concept of mystical experience and its main characteristics, the clasification of the phases of the Mystic Way, through the problem of the authenticity and unity of the mystical testimonies, step by step, including the context of magic, anthropological structures and psychology, are presented the fundamental features of Underhill’s theory of mysticism. The whole supplements her inspiring vision of the mistical future of the mankind.